Evaporation of ethanol-water sessile droplet of different compositions at an elevated substrate temperature. (December 2019) - Gurrala, Pradeep; Katre, Pallavi; Balusamy, Saravanan; Banerjee, Sayak; Sahu, Kirti Chandra
Highlights: Effects of composition and substrate temperature on evaporation of sessile binary droplets. Experiments are performed in a goniometer using cellulose acetate substrate. During evaporation droplet undergoes spreading, pinned and receding stages. Droplet lifetime exhibits non-monotonic trend with increasing ethanol concentration. Theoretical model is developed to predict the evaporation rates. Abstract: We experimentally investigate the evaporation dynamics of sessile droplets with different compositions of ethanol-water binary mixture at different substrate temperatures. At room temperature, a binary droplet undergoes two distinct evaporation stages unlike only the pinned stage evaporation for pure droplets. In the binary droplets, the more volatile ethanol evaporates faster leading to a nonlinear trend in the evaporation process. At elevated substrate temperature, we observed an early spreading stage, an intermediate pinned stage and a late receding stage of evaporation. Increasing the substrate temperature decreases the lifetime of binary droplets rapidly. At high substrate temperature, we found that the lifetime of the droplet exhibits a non-monotonic trend with the increase in ethanol concentration in the binary mixture, which can be attributed to the non-ideal behaviour of water-ethanol binary mixtures. Interestingly, the evaporation dynamics for different compositions at high substrate temperature exhibits a self-similar trend showing a constant normalised volumetric evaporation rate for the entire evaporation process. This indicates that the evaporation dynamics of a binary droplet of a given composition at high substrate temperature is equivalent to that of another pure fluid with a higher volatility at room temperature. The evaporation rates of pure and binary droplets at different substrate temperatures are compared against a theoretical model developed for pure and binary mixture droplets. The model predictions are found to be quite satisfactory for the steady evaporation phase of the droplet lifetimes.